Reseña: The many meanings of poverty: Colonialism, Social Compacts, and Assistance in Eighteenth-Century Ecuador - Jorge Moreno (Íconos)
Libro de Cynthia E. Milton, Stanford University Press, Stanford, 2007,356 págs.